A4 PERORAL ENDOSCOPIC MYOTOMY IS EFFECTIVE AND SAFE IN NON-ACHALASIA ESOPHAGEAL MOTILITY DISORDERS: AN INTERNATIONAL MULTICENTER STUDY. (1st March 2018) - Khashab, M; Masckauchan, M; Familiari, P; Draganov, P; Dakour Aridi, H; Cho, J; Ujiki, M; Rio Tinto, R; Louis, H; Desai, P; Velanovich, V; Albéniz, E; et al.
Abstract: Background: Peroral endoscopic myotomy (POEM) is an effective minimally invasive alternative modality to Heller myotomy for the treatment of achalasia. However, the efficacy of POEM in non-achalasia esophageal motility disorders has not yet been well demonstrated. These disorders include spastic esophageal conditions such as esophagogastric junction outflow obstruction (EGJOO), diffuse esophageal spasm (DES), and Jackhammer esophagus (JE). Aims: The objective of this international multicenter study was to assess the clinical outcomes of POEM in patients with non-achalasia disorders, namely DES, JE, and EGJOO, in a large cohort of patients. Methods: This was a retrospective study at 11 centers. Consecutive patients who underwent POEM for EGJOO, DES, or JE between January 2014 and September 2016 were included, patients with achalasia were excluded. Rates of technical success (completion of myotomy), clinical response (symptom improvement and Eckardt score ≤ 3), and adverse events (AEs, severity per ASGE lexicon) were ascertained. LES and cardia myotomy was performed in all cases, although it is unknown if this is essential in patients with DES and JE. Results: A total of 50 patients (56% female; mean age 61.7 years) underwent POEM for EGJOO (n=15), DES (n=17), and JE (n=18). Mean duration of symptoms was 53.2 months and most patients (68%) were treatment naïve. Technical success was achieved in all patients with a mean procedural time of 88.4 ± 44.7 min. The mean total myotomy length was 15.1 ± 4.7 cm. Clinical success was achieved in 93.3% of EGJOO and in 84.9% of DES/JE (p=0.41) with a median follow-up of 195 and 272 days, respectively. Chest pain improved in 88.9% of EGJOO and 87.0% of DES/JE (p=0.88). Mean Eckardt score decreased from 6.2 to 1.0 in EGJOO (p<0.001) and from 6.9 to 1.9 in DES/JE (p<0.001). A total of 9 (18%) AEs occurred and were rated as mild in 55.6% and moderate in 44.4%. These rates were comparable between both groups (13.3% vs 20%, p=0.58). Conclusions: POEM is effective and safe in the management of non-achalasia esophageal motility disorders, which include diffuse esophageal spasm, jackhammer esophagus, and esophagogastric junction outflow obstruction. Although AEs occurred in 18% of patients, none were severe and all complications were managed intraprocedurally or conservatively. Given that DES and JE do not typically have EGJ outflow obstruction, whether LES myotomy is required in these patients remains to be determined and warrants further investigation. Funding Agencies: None